Pengukuran Kinerja Perusahaan Pada Pt. Yyy Dengan Menggunakan Metode Balanced Scorecard - Richardson Harjanto Nurdin (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
This research aims to find out how the company performance of PT. YYY can be measured and evaluated by using the balanced scorecard method. The research using the balanced scorecard method aims to evaluate four important perspectives at PT. YYY which includes financial perspective, internal business process perspective, customer perspective, and growth and learning perspective in the period of the year 2013 to 2017.